Analysis of the Effect of Receivables Turnover, Inventory Turnover, And Liquidity on Profitability with Company Size as a Moderation Variable in Food and Beverage Companies on the Indonesia Stock Exchange (IDX) for the 2021-2024 Period - Muhammad Qolyuby; Acep Komara; Agung Yulianto (SAFE-Network, 2026)
This study aims to analyze the effect of receivables turnover, inventory turnover, and liquidity on profitability with firm size as a moderating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employs a quantitative approach using secondary data obtained from the companies’ annual financial statements. The population consists of 44 companies, and purposive sampling is applied to obtain 16 companies as research samples over four years of observation, resulting in 64 data observations. Data analysis techniques include descriptive statistics, classical assumption tests, and Moderated Regression Analysis (MRA). The results indicate that receivables turnover has a positive and significant effect on profitability, suggesting that more effective receivables management enhances a company’s ability to generate profits. Inventory turnover does not have a significant effect on profitability, indicating that inventory efficiency does not directly contribute to profit improvement. Liquidity has a negative and significant effect on profitability, implying that excessively high liquidity may reduce the efficiency of asset utilization in generating profits. Furthermore, firm size is proven to moderate the relationship between receivables turnover and profitability as well as between liquidity and profitability, but it does not moderate the relationship between inventory turnover and profitability. This study is expected to provide practical implications for company management and investors in making decisions related to working capital management and financial performance.